Analysing Gender in Performance
XIV, 322 p. 20 illus.
Keywords: Analysing Gender in Performance brings together the fields of Gender Studies and Performance Analysis to explore how contemporary performance represents and interrogates gender. This edited collection includes a wide range of scholarly essays, as well as artists’ voices and their accounts of their works and practices. The Introduction outlines the book’s key approaches to concepts in English language gender discourses and gender’s intersectionalities, and sets out the approaches to performance analysis and methods of research employed by the various contributors. The book focuses on performances from the Global North, staged over the past fifty years. Case studies are diverse, ranging from site-specific, dance theatre, speculative drag, installation, and music video performances to Mabou Mines, Churchill, Shakespeare and Ibsen. Contributors explore how gender intersects with sexuality, social class, race, ethnicity, indigeneity, culture and history. Read individually orin tension with one another, the essays confront the contemporary complexities of analysing gender in performance. J. Paul Halferty is Assistant Professor in Drama Studies at University College Dublin, Ireland. His research on queer theatre and performance in Canada and Ireland has been published in various journals and anthologies. Cathy Leeney is Research Active Assistant Professor in Drama Studies at University College Dublin, Ireland. Teaching, research and publications are in Gender in Performance, Women in Irish Theatre, and Staging Practices.